Combining phylogeography and landscape genetics of Xenopipo atronitens (Aves: Pipridae), a white sand campina specialist, to understand Pleistocene landscape evolution in Amazonia. (21st May 2013) - Capurucho, João Marcos G.; Cornelius, Cintia; Borges, Sergio Henrique; Cohn‐Haft, Mario; Aleixo, Alexandre; Metzger, Jean Paul; Ribas, Camila C.
<x xml:space="preserve">Abstract</x> Open vegetation (campinas and campinaranas) associated with white sand patches occurs in the form of islands in a forested matrix throughout the Amazon basin. Bird species restricted to these habitats have patchy distributions, although connectivity may have been influenced by past glacial cycles as a result of the substitution of forest by savanna. Because these landscape changes are a matter of debate in the history of Amazonia, we studied the diversification of Xenopipo atronitens, a white sand specialist, aiming to infer the effects of past climate changes. The split of Xenopipo atronitens from its sister species, Xenopipo uniformis, may be related to Tepuis erosion and retreat of escarpments during the Miocene, or to a dispersal event. Compared with birds from terra firme forest, X. atronitens has low genetic structure. Low levels of unidirectional gene flow were found from the Guyana Shield to adjacent areas. Demographic expansion starting approximately 25 kyr BP was detected for some populations and is probably related to the Last Glacial Maximum and subsequent climate improvement. Landscape genetic analyses indicate that the forested (terra firme) matrix acts as a barrier for the dispersal of X. atronitens. The results of the present study indicate that glacial cycles have deeply influenced Amazonian biogeographical history, demonstrating a complex interaction between forest and nonforest habitats during the Pleistocene. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 110, 60–76.